Increasing Knowledge and Behavioral Change in Handling and Prevention of Gout Through Counseling in Antang Village, Manggala District, South Sulawesi - Rismawati Kadir; Rizkia Djohar; Irmawati; Almaida; Maya Apriliah Ruslan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Gout has become a significant health problem in Indonesia, including in Antang Village. This disease can cause joint pain, swelling, and serious complications if left untreated. This research aims to see the effect of counseling on gout disease by increasing knowledge and changing the behavior of people in the Antang Village. The method used is a descriptive method with a qualitative approach. The sampling technique used was purposive sampling, involving nine respondents who met the criteria of being elderly and suffering from gout. The sources of data in this study came from interviews with respondents, direct observation, and medical records. This research was conducted within one week in Antang Village, Manggala District. The results showed that counseling on gout disease was effective in increasing public knowledge in Antang Village.